Effects of Nandrolone Decanoate and Exercise on Histological Structures of Soleus Muscle of the Female Rat - Usmanullah, Muhammad Waqar, Dost Muhammad Khan, Nayyer Uz Zaman, Muhammad Hanif, Jamshed Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Nandrolone Decanoate (ND) as most frequently used as performance enhancing drug, the present study was conducted to investigate the histological changes produced by ND alone and in combination with exercise on soleus muscle. Forty female rats were divided equally by randomized control trial (RCT)i.e BI (control), BII (ND5mg/kg intramuscular twice weekly) BIII (Exercise/swimming) BIV (ND & Exercise) for 12 weeks at the animal house of PGMI, Lahore during the year 2010. Data was recorded on various microscopic parameters viz; internalization of nuclei, splitting in muscle fibers, rounded or angular muscle fibers and diameter of fibers for control and experimental groups.Results regarding internalization of nuclei revealed significant (P≤0.006, 0.013) differences among the groups receiving ND in comparison to control and exercise and highly significant (P≤0.001)differences were observed in animals subjected to ND and exercise in comparison to control. Splitting of muscle fiber was observed in group BIII and BIV (P≤0.001) in comparison with control. Significant increase in diameter of muscle fiber was observed in group BIII (P≤0.005) and BIV (P≤0.001) in comparison to control.Similarly, minimum degenerative changes were observed showing angular or rounded fibers in group BIII andBIV in comparison to control. The instant results suggest that significant hypertrophy was observed in animals subjected to ND and exercise. Keywords: Soleus, splitting, diameter, internalization of nuclei, female